INVESTMENT RISK IN CRYPTOCURRENCY TRANSACTIONS IN INDONESIA - Agustina, Elvira (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2023)
This research was conducted on Investment Risk in Cryptocurrency Transactions in Indonesia. The purpose of this study is to find out how the risks of investing and cryptocurrency transactions in Indonesia are. Source of data in this study using secondary data. Then using a qualitative descriptive research type because researchers want to find facts about "Investment risks in cryptocurrency transactions in Indonesia" to accurately convey what are the risks of investing in cryptocurrency transactions through several phenomena that occur. In this case, the research location is carried out, namely from the phenomena described on the website obtained from the Data Box which discusses developments and activities in cryptocurrency with hypotheses (allegedly Investment Risk Affects Cryptocurrency Transactions in Indonesia). Based on the results of the discussion, it can also be concluded that investing in cryptocurrency has a fairly high risk, because cryptocurrency price movements are a bubble or momentary enthusiasm, lack of regulation, still leaves legality issues, becomes the target of cybercrime and has a dependence on technology.